Muscle hypertrophy and pseudohypertrophy. Issue 5 (4th August 2017) - Walters, Jon
Abstract : The physical examination always begins with a thorough inspection and patients with potential neuromuscular weakness are no exception. One question neurologists routinely address during this early part of the assessment is whether or not there is muscle enlargement. This finding may reflect true muscle hypertrophy—myofibres enlarged from repetitive activity, for example, in myotonia congenita or neuromyotonia—or muscles enlarged by the infiltration of fat or other tissue termed pseudohypertrophy or false enlargement. Pseudohypertrophic muscles are frequently paradoxically weak. Recognising such a clinical clue at the bed side can facilitate a diagnosis or at least can narrow down the list of potential suspects. This paper outlines the conditions, both myopathic and neurogenic, that cause muscle enlargement.